Alfabetização digital mediada por tablets para crianças e adolescentes em tratamento oncológico - Weizenmann, Carlos Eduardo (2015)
The use of mobile technologies becomes ever more present and necessary in our lives, either for routine activities or education. Based on this argument, this dissertation aims to analyze the possible contribution of using tablet as a tool to develop different methodologies for digital literacy, thus providing inclusion in the "technological world". The use of technological resources (tablet) has become a necessary tool to assist teaching and learning process of children and adolescents. For this reason, it is important to conduct a qualitative study using the method of action research by allowing greater involvement with its object, through which the researcher is part of the field of research. We offered workshops divided into two modules: the first one for free adaptation to the tablet and the second one for using resources in various activities aiming at ludicity. The data collection system was carried out in two stages: before the beginning of the workshops and at the end of module II. The final product of this work was the creation of a virtual repository, of open access, that will be inserted in the blog of the workshop so that there is greater awareness of the work developed, which can be used by the students after the end of the workshops, facilitating interaction, cooperation and collaboration among the group. The contributions of this work aimed at the insertion of the mobile technologies to contribute to the participants medical treatment. This study belongs to the research line: Desenvolvimento de Tecnologias Educacionais em Rede, and the research project O uso de tecnologias móveis (tablets), no processo de ensino e aprendizagem da alfabetização digital e língua espanhola, com crianças e adolescentes em tratamento oncológico, approved in December 13, 2014, under the number 912.827.